2021
DOI: 10.1002/adma.202104962
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Complementary Zwitterionic Peptides Direct Nanoparticle Assembly and Enable Enzymatic Selection of Endocytic Pathways

Abstract: Supramolecular self‐assembly in biological systems holds promise to convert and amplify disease‐specific signals to physical or mechanical signals that can direct cell fate. However, it remains challenging to design physiologically stable self‐assembling systems that demonstrate tunable and predictable behavior. Here, the use of zwitterionic tetrapeptide modalities to direct nanoparticle assembly under physiological conditions is reported. The self‐assembly of gold nanoparticles can be activated by enzymatic u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 69 publications
0
32
0
Order By: Relevance
“…Huang et al recently demonstrated the MMP-9-triggered assembly of gold nanoparticles via electrostatic interactions following MMP-mediated dePEGylation. These nanoparticles underwent endocytosis and induced cytotoxicity in the MMP-9-expressing cells where inverting just two amino acids in this sequence inactivated the enzyme-responsiveness, self-assembly, and cellular uptake . Enzyme-directed nanoparticle self-assembly at a tumor site was also used for in vivo cancer imaging based on kinetic trapping of the assembled particles within the tumor .…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al recently demonstrated the MMP-9-triggered assembly of gold nanoparticles via electrostatic interactions following MMP-mediated dePEGylation. These nanoparticles underwent endocytosis and induced cytotoxicity in the MMP-9-expressing cells where inverting just two amino acids in this sequence inactivated the enzyme-responsiveness, self-assembly, and cellular uptake . Enzyme-directed nanoparticle self-assembly at a tumor site was also used for in vivo cancer imaging based on kinetic trapping of the assembled particles within the tumor .…”
Section: Introductionmentioning
confidence: 99%
“…The design of active sites based on artificial systems via using the concept of supramolecular assembly is the key to gain further insight into the natural evolution of enzymes. [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] 2.1 Peptide based self-assembly as esterase Esterase and in particular carbonic anhydrases (CAs) are among the ubiquitous metalloenzymes that regulate various physiological functions along with implications in the field of biotechnology. [72][73][74] Despite numerous efforts for artificially fabricating CA mimics, the complex folding patterns and the stability of the peptide building blocks pose tremendous hurdles.…”
Section: Peptide Assemblies For Diverse Enzymatic Transformationsmentioning
confidence: 99%
“…The design of active sites based on artificial systems via using the concept of supramolecular assembly is the key to gain further insight into the natural evolution of enzymes. 53–71…”
Section: Peptide Assemblies For Diverse Enzymatic Transformationsmentioning
confidence: 99%
“…[32] Copyright 2021, The Royal Society of Chemistry. Internal stimuli pH-responsive PEG, TEG Inward diffusion [47,100,118,123,126,129] Redox-responsive PEG Inward diffusion [56,136,156] Enzyme-responsive ALG Cross-linking-codependent [14,27,106,124,130,132,158] Electroresponsive PLGA, PEG Inward diffusion [70,146,196] ROS-responsive PEG, PLGA Self-assembled [149,150,160,162,165] External stimuli Thermoresponsive PEG, PLGA In situ formation [7,30,34,42,67,170,171,173,175,17 8,181] Light-responsive PLGA, ALG Self-assembled [9,28,113,183,185] Magnetic-responsive ALG, HA Cross-linking-codependent [29,166,193,194,195] Mechanoresponsive PEG, PCL Inward diffusion [146,148,197,199,200] Ultrasound-responsive PEG Inward diffusion [14,163,201,…”
Section: Ph-responsive Nanocomposite Hydrogelsmentioning
confidence: 99%